HUBUNGAN ASI EKSKLUSIF, POLA MAKAN, DAN VARIAN MAKANAN DENGAN PICKY EATERS PADA ANAK USIA 1-3 TAHUN - Ulva Noviana (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Picky eaters is children who have behavior of refusing the type or group of food and difficultto accept new types of food so that children haveproblems of growth and development.Preliminary study results from 10 respondentsshowed that 6 people had low picky eaters and 4moderate picky eaters. The purpose of this studyis to analyze the relationship between exclusivebreastfeeding,diet, food variants with picky eater The design of this research is analytic withcross sectional approach. Independent variablesare Exclusive Breastfeeding,diet and foodvariants. Dependent variable is Picky Eaters. Thepopulation is 30 respondents.Taken samples are28 respondents. Sampling technique used in thisstudy was systematic random sampling.Instrument in this research is questionnaire andcheck list. Statistical test of diet and food variantsused Spearman Rank, exclusive breastfeedingused Chi Square with α ≤ 0.05. The result of statistical test using ChiSquare and Spearman Rank test for relationshipbetween exclusive breastfeeding ( ASI Exclusive)and Picky Eaters was obtained Pvalue equal to0,045 (0,045 <0,05). While dietary associationand picky eaters were obtained Pvalue equal to0,042 (0,042 <0,05). For the relationship betweenfood variant and picky eaters were obtainedPvalue equal to 0,040 (0,040 <0,05). All threeabove have lower significant than the degree of error. It can be concluded that Ho is rejected andHa accepted so there is relationship betweenexclusive breastfeeding ,diet, food variants with picky Eaters on children aged 1-3 years.